Clinical and Nutritional Follow-up of Cats with Chronic Kidney Disease Fed with a Renal Prescription Diet - Schaefer, Gabriela da Cruz; Vidor, Silvana Bellini; Jeremias, Juliana Toloi; Ferreira Pontieri, Cristiana Fonseca; Brunetto, Marcio Antonio; da Costa, Fernanda Vieira Amorim (Acta Scientiae Veterinariae, 2021)
Background: The use of prescription diets for cats with chronic kidney disease (CKD) is one of the main management approach of this disease in cats, and is considered a renoprotective strategy that may promote increased survival and/or improve quality of life, according to the stage of CKD. Besides that, nutritional assessment is important to monitor the maintenance of quality of life of the patients and their response to disease, especially those with chronic conditions. The aim of this study was to follow the clinical and nutritional status of cats with chronic kidney disease (CKD) IRIS stages II, III and IV fed with a renal prescription diet, followed for 12 months. Materials, Methods & Results: Patients were fed exclusively with a dry renal prescription diet and medications for the management of CKD were prescribed when needed. Exclusion criteria were cats that already received a renal prescription diet or medications for the treatment of CKD. Cats were evaluated every 2 months, considering body weight (BW), body condition score (BCS), muscle mass score (MMS), clinical and laboratory parameters. In all assessments, a complete blood count and biochemistry were performed by conventional methods with the patient fasted for 12 h. In addition, urinalysis, urinary protein:creatinine ratio (UPC) and urine culture were performed from a urine sample collected by cystocentesis. The quantitative variables were tested for their stability on consecutive assessments using the non-parametric Friedman test, and did not present significant variation during follow-up, except for systolic blood pressure (SBP). Eight cats with a diagnosis of CKD were included in the study and 6 of them remained in the same CKD stage during follow-up. On cat died due to an unrelated CKD cause. Regarding nutritional assessment, 5 of 7 cats maintained BW during the 12 months. Of these, 4 also maintained MMS and BCS. Three of 7 cats presented a decrease in MMS, 2 of which presented also a decreased BW and one maintained BW. Discussion: IRIS staging results combined with Friedman’s analysis demonstrated that the diet and the clinical management were effective in the non-progression of CKD in this study. As renal injury is not expected to be reversed in CKD, the maintenance of cats in the same IRIS stages and the minimum variation of the parameters is considered a positive result in this study. Hypertensive cats started on antihypertensive therapy during the study, achieving adequate control of SBP in most cases, what can justify the variation of this clinical parameter over the 12 months. Hyperphosphatemia was a frequent alteration, included stage II cats, and presented a positive response to nutritional and medical therapy. Despite CKD staging progression was not observed in most cats using serum creatinine as a single parameter, some cats presented BW and MMS reduction, which may have influenced this result. Weight loss and muscle wasting may have occurred by several reasons, including periods of hyporexia, presence of concomitant diseases, aging process or reduced protein content on renal prescription diets. This study enhances the importance of the association of clinical and nutritional management in the maintenance of cats with CKD. We suggest that other studies are done during longer periods of time and with a larger sample to support the results found. We also suggest new studies to evaluate the protein requirements for cats with CKD.